2010
DOI: 10.1007/s00775-010-0641-2
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and computational investigation of three Cys-to-Ser mutants of nickel superoxide dismutase: insight into the roles played by the Cys2 and Cys6 active-site residues

Abstract: Nickel-dependent superoxide dismutase (Ni-SOD) is a member of a class of metalloenzymes that protect aerobic organisms from the damaging superoxide radical (O 2 ·− ). A distinctive and fascinating feature of NiSOD is the presence of active-site nickel-thiolate interactions involving the Cys2 and Cys6 residues. Mutation of one or both Cys residues to Ser prevents catalysis of O 2 ·− , demonstrating that both residues are necessary to support proper enzymatic activity (Ryan et al., J Biol Inorg Chem, 2010). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 128 publications
(160 reference statements)
2
18
0
Order By: Relevance
“…Recent mutagenesis studies by Maroney and Brunold on Ni-SOD at Cys2, Cys6 and Cys2/Cys6 (double mutant) have shown that even the absence of one cysteine thiolate promotes high-spin ( S =1) aquated Ni(II) complexes at the Ni-SOD active site with no evidence of the remaining Ni-SCys bond in the single mutants . 21,23 This finding in combination with the results reported here suggests more than redox-modulation/H-storage roles for cysteine in Ni-SOD. We propose that both Cys6 and Cys2 ligands in Ni-SOD are crucial for proper active site assembly and stabilization of the low-spin square-planar Ni(II) state.…”
Section: Propertiessupporting
confidence: 67%
See 1 more Smart Citation
“…Recent mutagenesis studies by Maroney and Brunold on Ni-SOD at Cys2, Cys6 and Cys2/Cys6 (double mutant) have shown that even the absence of one cysteine thiolate promotes high-spin ( S =1) aquated Ni(II) complexes at the Ni-SOD active site with no evidence of the remaining Ni-SCys bond in the single mutants . 21,23 This finding in combination with the results reported here suggests more than redox-modulation/H-storage roles for cysteine in Ni-SOD. We propose that both Cys6 and Cys2 ligands in Ni-SOD are crucial for proper active site assembly and stabilization of the low-spin square-planar Ni(II) state.…”
Section: Propertiessupporting
confidence: 67%
“…In fact, site-directed mutagenesis of the Cys-S ligands of Ni-SOD suggest that even mutation of one cysteine to serine promotes a high-spin ( S = 1) octahedral Ni(II) site with no S-ligands (replaced by H 2 O). 21,23 When one mol-equiv of the corresponding thiolate is added to these D 2 O solutions, however, the NMR became well-resolved with defined peaks that are consistent with monomeric ( S = 0) [Ni(GC-OMe)(SR)] − complexes (Figure 1 for 2 , Supporting Information for 3–5 ). Indeed, ESI-MS − analysis of as-isolated 2 and 4 dissolved in protic solvents revealed ions corresponding to [Ni 2 (GC-OMe) 2 (SR)] − , [Ni 3 (GC-OMe) 3 (SR)] − and [Ni 4 (GC-OMe) 4 (SR)] − in addition to those of the parent ion (Figures S20–27).…”
Section: Propertiesmentioning
confidence: 99%
“…Such high-spin Ni(II) centers have also been observed in Cys-to-Ser mutants of NiSOD, which are catalytically inactive. (14, 27) The formation of a high-spin six-coordinate complex for the disordered “Ni-hook” domain may also sterically prevent folding into the “Ni-hook” structure that features a His1 imidazole-Glu17 H-bond, a possible explanation for why exogenous imidazole does not complement the loss of the His1 imidazole ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the nickel ligands in NiSOD in those features has been addressed using a mutagenic approach, which has resulted in a number of mutant proteins with lower catalytic activity. 81 , 89 , 96 The activities of mutant NiSODs have been reviewed. 81 , 97…”
Section: Nickel Superoxide Dismutasementioning
confidence: 99%